INQUIRY BASED LEARNING MODULE BASED ON SCIENCE OBJECT MATERIAL AND OBSERVATION OF ODD SEMESTER GRADE VII OF SMP/MTS - REVA YOLANDA; Hardeli Hardeli (Universe, 2020)
ABSTRACT This research discussed the Development of Inquiry Based Learning Module Based on Science Object Material and Observation of Odd Semester Grade VII of SMPN 13 Padang. This study aims to produce inquiry-based modules that can help students increase their interest in learning and independent learning in understanding subject matter, as well as investigating validity and practicality. This type of the research is the Ploomp development model which consists of three stages, namely preliminary research, prototype stage, and assessment phase. The research instrument was a questionnaire. The Observation was validated by a validator consisting of 2 lecturers at the Natural Sciences of UNP, and 2 science teachers at SMPN 13 Padang. The Practicality Test was conducted by science teachers and students of class VII at SMPN 13 Padang. Based on the results of the research conducted, an inquiry based learning module was obtained. The Product research by teachers based on the average ease of use of validity ,the efficiency of learning time and the benefits of using validity module are very high. The Product research by students based on average ease is very high. © Department of Science Education, Universitas Negeri Padang Keywords: module, the object of natural science and its observations, and inquiry based learning.